Measuring is knowing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Monitoring nutrient flows and economic performance in tropical farming systems (NUTMON) Alterra Agricultural Economics Research Institute, LEI, (manual annex CD Rom), Wageningen UR, 2001. ISBN 90 327 0303 x Euro 250 per set but free for univer